Koumine supplementation positively affects growth, circadian rhythms, and stress levels in Cyprinus carpio - Dongjie Wang; Bin Ye; Qiujie Wang; Jiayang He; Zhiheng Zuo; Xiang Li; Jixing Zou; Shaolin Xie (Aquaculture Reports, 2023)
This study evaluated the effects of koumine on growth performance, brain transcriptional response, expression of genes associated with circadian rhythms, and physiological stress indicators in carp (5.21 ± 0.05 g). Fish were fed four different koumine levels (0, 0.2, 2, and 20 mg/kg) of diet (crude protein 29.71%, crude lipid 3.68%) for 10 weeks in a RAS (26.0–28.0 ℃, pH 7.3–7.5, and DO 5.5–6.1 mg/L). Each type of feed was administered to three replicate tanks (50 L, 12 cycles per day), each containing 30 fish, with feeding occurring twice daily. The results showed that koumine supplementation improved the growth performance of carp. Significant enrichment of circadian rhythm, memory, and behavior-related pathways in the brain of the koumine-supplemented group of fish. The circadian rhythm positive feedback-related genes MKP5, ATP1A, ATP2A, and CRY2 were significantly upregulated (P < 0.05), and the negative feedback-related genes REV-ERBA were significantly downregulated (P < 0.05) in the koumine supplementation group. The fish in the koumine group showed a significant increase in brain dopamine concentrations (P < 0.05) and a significant decrease in 5-hydroxytryptamine concentrations (P < 0.05). Overall, our study showed that koumine supplementation improved growth performance and reduced stress levels during rearing of carp, which may be related to the regulation of expression of circadian rhythm-related pathways.